Integrasi Nilai-nilai Pendidikan Keluarga Islami Melalui Bab Nikah dalam Kitab Rawai’ul Bayan Fi Tafsir Ayatil Ahkam di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: Integration of Islamic Family Education Values Through the Marriage Chapter in the Book of Rawai'ul Bayan Fi Tafsir Ayatil Ahkam at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School, Surakarta - Isa Mahendra, Isa Mahendra; Fa’iz Ahmad Nurdiansyah; Salma Rahmawati; Lu’luil Maknunah (DIRASAH: Jurnal Kajian Islam, 2026)
This research employs a qualitative approach through an interview with a resource person who has studied and mastered traditional Islamic texts (kitab kuning), particularly Rawai‘ul Bayan. The findings show that the Nikah chapter does not only discuss formal legal aspects—such as the pillars and conditions of marriage, guardians (wali), dowry (mahar), and the rights and obligations of spouses—but also contains profound educational values for Islamic family life. These include values of responsibility, justice, love and compassion (mawaddah wa rahmah), communication, patience, and moral ethics in family building. Such values are essential for creating a harmonious and blessed family (sakinah, mawaddah, wa rahmah) as taught in the Qur’an. The application of these teachings in the pesantren environment helps students not only understand marriage law theoretically but also practice it in real life. In the context of modern society, which faces moral and social challenges, the teachings from Rawai‘ul Bayan remain highly relevant as a guide to forming Islamic families grounded in harmony, ethics, and faith.